(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
Financial jargon in the capital markets refers to the specialized vocabulary used by professionals (such as investors, traders, analysts, and financial managers) in the buying, selling, and trading of securities. The capital markets, consisting of both equity markets (stock markets) and debt markets (bond markets), involve complex transactions and instruments that require precise terminology for effective communication. Understanding this jargon is essential for anyone working in or studying capital markets, as it helps in analyzing market conditions, making informed investment decisions, and managing risks.Key concepts include equity, representing ownership in companies through stocks, and bonds, which are debt instruments used by issuers to raise capital